Church Fathers on Ownership - Chmielarz,Małgorzata, Ilski Kazimierz (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The study aims at an analysis on the concept of ownership in the selected Church Father's works. The authors focus on the work of Saint Jerome Saint Basil of Caesarea, Ambrose and Augustine, presenting the concept of ownership in the middle ages.
Keywords: Church Fathers; ownership; middle ages